2018
DOI: 10.1016/j.actpsy.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Improving novel motor learning through prior high contextual interference training

Abstract: The primary objective of the present experiment was to examine the influence of recent practice in a random and blocked format for future motor learning. First, individuals practiced three unique discrete sequence production tasks in either a blocked or random schedule. One day later, all individuals practiced a new motor sequence not previously practiced. On day three, mean total time for the test performance of the original three motor sequences was lower for individuals that practiced in a random format. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 37 publications
6
17
0
Order By: Relevance
“…Following RP, in contrast, there was a significant increase in response time over the 24-h period, suggesting that low contextual interference provides for less stabile representation of the practiced motor sequence. This finding is consistent with previous demonstrations that IP establishes stability in motor memory representations while RP typically results in forgetting in the period following training (e.g., Kim et al, 2018).…”
Section: Long-term Performance and Prefrontal Cortex Recruitment Following High And Low Contextual Interference Practice Conditionssupporting
confidence: 93%
“…Following RP, in contrast, there was a significant increase in response time over the 24-h period, suggesting that low contextual interference provides for less stabile representation of the practiced motor sequence. This finding is consistent with previous demonstrations that IP establishes stability in motor memory representations while RP typically results in forgetting in the period following training (e.g., Kim et al, 2018).…”
Section: Long-term Performance and Prefrontal Cortex Recruitment Following High And Low Contextual Interference Practice Conditionssupporting
confidence: 93%
“…Other studies concerning the CI effect in novel motor skill learning found that prior experience with interleaved practice improved new motor task acquisition, however, delayed retention was unaffected by practice schedule (Hodges et al, 2014;Kim et al, 2016Kim et al, , 2018. Hodges et al (2014) found that random practice experience, compared with blocked practice, led to better acquisition of three novel motor skills after a oneday delay and mitigated the low accuracy cost usually associated with random practice, but ultimately did not affect retention.…”
Section: Implicit Motor Sequence Transfermentioning
confidence: 92%
“…This task typically involves two fixed series of 6 or 7 successive key presses. Learning these discrete motor sequences has previously been found to also benefit from high CI (Cross et al, 2007;Immink & Wright, 1998;Kim et al, 2018). CI research with the DSP task has the advantage that predictions can be tested using the Cognitive framework for Sequential Motor Behavior (C-SMB, Verwey et al, 2015, which extended the Dual Processor Model, Abrahamse et al, 2013).…”
Section: Discrete Motor Sequences and C-smbmentioning
confidence: 99%